Benchmarking diamond surface preparation and fluorination via inductively coupled plasma-reactive ion etching - Gray, Tia; Zhang, Xiang; Biswas, Abhijit; Terlier, Tanguy; Oliveira, Eliezer F. [UNESP]; Puthirath, Anand B.; Li, Chenxi; Pieshkov, Tymofii S.; Garratt, Elias J.; Neupane, Mahesh R.; Pate, Bradford B.; Birdwell, A. Glen; et al. (Elsevier, 2024)
Diamond, renowned for its exceptional semiconducting properties, stands out as a promising material for high-performance power electronics, optics, quantum, and biosensing technologies. This study methodically investigates the optimization of polycrystalline diamond (PCD) substrate surfaces through Inductively Coupled Plasma Reactive Ion Etching (ICP-RIE). Various parameters, including gaseous species, flow rate, coil power, and bias power were tuned to understand their impact on surface morphology and chemistry. A thorough characterization, encompassing chemical, spectroscopic, and microscopic methods, shed light on the effects of different ICP-RIE conditions on surface properties. CF4/O2 plasma emerged as a viable treatment for achieving smooth PCD surfaces with minimal etch pit formation. Most notably, surface fluorination, a critical aspect of increasing chemical and thermal stability, was successfully accomplished using CF4, SF6, and other F-containing plasmas. The fluorine concentration and surface chemistry variations were studied, with high resolution X-ray Photoelectron Spectroscopy unveiling differences amongst the sp2 C phase, sp3 C phase, C–O, C[dbnd]O, and C–F bonds. Time-of-flight secondary Ion Mass Spectrometry (ToF-SIMS) and depth-profile analysis unveiled a consistent surface fluorination pattern with CF4/O2 treatment. Furthermore, contact angle measurements showcased heightened hydrophobicity. This study provides valuable insights into precise diamond surface engineering, important for the development of future diamond-based semiconductor technologies.
Keywords: Contact angle; Diamond; Fluorination; Reactive ion etching; Surface morphology